Eradication versus control of Mediterranean fruit fly in Western Australia. (10th December 2014) - Cook, David C.; Fraser, Rob W.
Abstract The primary chemicals used by Western Australia's horticultural industries with respect to field control and post‐harvest disinfestation procedures for the Mediterranean fruit fly are soon to be withdrawn from use because of public health concerns. When this occurs, the necessary switch to alternative control methods such as bait sprays and intensive fruit fly trapping will involve additional producer costs. The present study demonstrates that these costs are likely to exceed the costs of eradication using the sterile insect technique. Given this result, eradication cost sharing arrangements between government and industry are discussed that could produce mutual benefits in the long term.